RECOMENDAÇÕES PARA O USO DE TECNOLOGIAS SUSTENTÁVEIS EM EDIFÍCIOS INSTITUCIONAIS NA UFV - Tiburcio, Tulio M S; Lemos, Mariana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Sustainability is one of the most discussed themes and fundamental for a balanced development. It is essential for producing good architecture, obeying social equity, ecological prudence and economic efficiency. In architecture, the incorporation of technologies aimed at sustainability has increased due to the need to preserve and conserve the environment in which we live in. In institutional buildings, there is still little use or even the absence of sustainable technologies. Sometimes it disobeys the criteria of ecological prudence and economic efficiency, contradicting the role that these places should perform in society, as examples for more conscious buildings. This research aimed to investigate the incorporation of sustainable technologies in institutional buildings. As methodology case studies were used to map which technologies has been inserted in new buildings at the Federal University of Viçosa, Brazil. Results shown that these buildings had adopted some technologies, however the implementation was not satisfactory. Recommendations were listed to adapt or to design new buildings within the sustainable technologies approach.